Biochemical markers of coronary atherosclerosis: building models and assessing their prognostic value regarding the lesion severity - M. V. Zhatkina; V. A. Metelskaya; N. E. Gavrilova; E. B. Yarovaya; Yu. K. Makarova; O. A. Litinskaya; N. L. Bogdanova; B. A. Rudenko; O. M. Drapkina (Российский кардиологический журнал, 2021)
Aim. To assess the individual and complex prognostic value of various blood biochemical parameters (biomarkers) in the non-invasive diagnosis of coronary artery (CA) atherosclerosis.Material and methods. The study included 216 patients (men, 115; women, 101) aged 24 to 87 years (mean age, 61,5±10,7 years), who underwent indicated coronary angiography. All patients underwent a biochemical blood tests to determine the parameters of lipid, carbohydrate and nitrogen metabolism, the hemostatic system, inflammatory markers, as well as the creatinine level as an indicator of renal function.Results. Analysis revealed biomarkers, the deviations in the level of which contribute to the diagnosis and determination of the coronary involvement. These biomarkers include glucose, creatinine, C-reactive protein, and adiponectin. Using these biochemical parameters, a multivariate model (MVM) was constructed, which was significant for the diagnosis of coronary atherosclerosis and determination of its severity. With the help of ROC-analysis, the cutoff point of MVM of 2 was found. MVM >2 with a sensitivity of 72% indicate CA atherosclerosis of any severity, as well as with a specificity of 62,5%, it can be ruled out. Using MVM data and a cutoff point of 2, a binary logistic regression model was built, according to which, with a MVM >2, the odds for detecting CA atherosclerosis of any degree is 2,1 times higher (95% confidence interval (CI), 1,2-3,8; p=0,010), severe CA — 4,7 times (95% CI, 1,9-12,0; p=0,001) compared with individuals with MVM ≤2, who have 2,8 times (95% CI, 1,4-4,9; p=0,002) a higher chance of detecting intact CAs.Conclusion. Thus, the total MVM score of 0-2 indicates the absence of coronary atherosclerosis, while 3-4 points -CA atherosclerosis of any severity.